2016
DOI: 10.7900/jot.2015may20.2062
|View full text |Cite
|
Sign up to set email alerts
|

Partial orders on partial isometries

Abstract: Abstract. This paper studies three natural pre-orders of increasing generality on the set of all completely non-unitary partial isometries with equal defect indices. We show that the problem of determining when one partial isometry is less than another with respect to these pre-orders is equivalent to the existence of a bounded (or isometric) multiplier between two natural reproducing kernel Hilbert spaces of analytic functions. For large classes of partial isometries these spaces can be realized as the well-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…This analysis, having its original source in a classical paper of Livsic [7], also draws on subsequent work in [1,5,8]. Among other things, three preorder relations are introduced in [3]; each of these induces an equivalence relation, and one of the questions addressed is when the classes of equivalence are precisely the classes of unitary equivalence. It is shown that the question can be rephrased as the existence of certain multipliers between model spaces (in the sense of [2] or [10]), and partial results are obtained.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis, having its original source in a classical paper of Livsic [7], also draws on subsequent work in [1,5,8]. Among other things, three preorder relations are introduced in [3]; each of these induces an equivalence relation, and one of the questions addressed is when the classes of equivalence are precisely the classes of unitary equivalence. It is shown that the question can be rephrased as the existence of certain multipliers between model spaces (in the sense of [2] or [10]), and partial results are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The starting point for this note is the paper [3], which makes a detailed analysis of the class of completely nonunitary partial isometries on a complex separable Hilbert space with equal defect indices (finite or infinite). This analysis, having its original source in a classical paper of Livsic [7], also draws on subsequent work in [1,5,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recall here, that the classes of partial isometries and symmetric linear transformations on Hilbert space are equivalent under a natural bijection, the Cayley Transform, a fractional linear transformation of the closed complex upper half-plane onto the closed unit disk (minus the point {1}) [1,Chapter VII]. In [2,24,40], several key aspects of these approaches were combined and slightly generalized with the introduction of the concept of a model map for a symmetric linear transformation or partial isometry with equal defect indices [2, Section 2.1], [24,Section 3], [40,Definition 5.1].…”
Section: Introductionmentioning
confidence: 99%
“…A linear transformation T belongs to S if and only if T ≃ T Γ for some measure Γ obeying the Herglotz condition(23).…”
mentioning
confidence: 99%